Criminal justice ethics: theory and practice - Banks, Cyndi (Sage, 2025)
"This work examines the relationship between criminal justice and ethics, offers ethical theories, and then applies those ideas to various aspects of the criminal justice system. Now in its sixth edition, this version upholds the critical viewpoint used in past editions by challenging, analyzing, and offering modes of resolving historical and contemporary ethical problems as they pertain to and provide context to today's criminal justice system. It is crucial to identify the many ethical dilemmas that arise in the criminal justice system. Chapters 1 through 10 make clear that professionals operating inside the system can face a range of ethical problems and moral dilemmas. These chapters first set the scene for the many circumstances that professionals encounter inside the various facets of the system, situations that necessitate a comprehension of ethical decision-making. Accordingly, the format of this book is intentionally inverted to ground students in the practical issues prior to wrestling with ethical theory and the application of those theories to ethical issues occurring within the system. Those instructors who prefer to focus on philosophical theory prior to examining the ethical issues that arise in the system are encouraged to reverse the order of assigning chapters of the book to students to accomplish their pedagogical goals. This new edition is the result of an in-depth review of the fifth edition and contains an abundance of fresh information that helps contextualize and identify ethical dilemmas. It incorporates research and studies that have been published since the fifth version was released. This latest edition maintains its status as an authoritative, accessible, and scholarly source of knowledge on the intersection of ethics and criminal justice. The changes in this edition include the following:"--